1991
DOI: 10.1002/ange.19911031014
|View full text |Cite
|
Sign up to set email alerts
|

Erzeugung von kolloiden Übergangsmetallen in organischer Phase und ihre Anwendung in der Katalyse

Abstract: Durch Reduktion von Metallsalzen mit Tetraalkylammoniumhydrotriorganoboraten in organischer Phase können Metallkolloide der Elemente der Gruppen 6‐11 erhalten werden. Auf Trägeroberflächen adsorbiert sind diese Metallkolloide hochwirksame Hydrierkatalysatoren, deren Aktivität sich noch durch Dotierung mit niedervalenten Organotitanverbindungen steigern läßt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0
4

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(43 citation statements)
references
References 3 publications
1
38
0
4
Order By: Relevance
“…Colloidal Pt on a carbon support (carbon as received or oxidized) was prepared for us by B6nnemann et al [18] PtCI 2 is suspended in THF and reduced with (N(octyl)4BEt3H), where the ammonium salt functions as a stabilizer for the colloidal metal particles.…”
Section: Colloidal Catalystmentioning
confidence: 99%
“…Colloidal Pt on a carbon support (carbon as received or oxidized) was prepared for us by B6nnemann et al [18] PtCI 2 is suspended in THF and reduced with (N(octyl)4BEt3H), where the ammonium salt functions as a stabilizer for the colloidal metal particles.…”
Section: Colloidal Catalystmentioning
confidence: 99%
“…Great efforts have been made to explore suitable synthetic routes by many investigators. Petrow and Allen [8], Watanabe and Saegusa [9], and Bönnemann et al [10] developed colloidal deposition routes to prepare Pt electrocatalysts with high metal surface areas. Lasch et al [11] obtained highly active unsupported Pt and PtRu alloy electrocatalysts by a modified Adams method.…”
Section: Introductionmentioning
confidence: 99%
“…[10,13] Pre-prepared colloidal alloy particles, covered by various protecting shells, offer a different means of access to highly dispersed bimetallic catalyst precursors. [14][15][16][17][18][19] Following the so called ''precursor concept'', [20] these pre-prepared nanometals, for which the particle size distribution, composition and structure are rather well defined, may be deposited on 819 distribution. The physical characterisation by a combination of several techniques has shown that the SiO 2 -embedded Pd/ Au colloid preserves the size and the structural characteristics of the colloidal metal precursor.…”
mentioning
confidence: 99%
“…[18][19][20][21] Here we report the preparation of a heterogeneous Pd/Au catalyst formed by the embedding of preprepared tetraalkylammonium-stabilized Pd/Au alloy particles in a solid SiO 2 matrix following a modified sol-gel process.…”
mentioning
confidence: 99%
See 1 more Smart Citation